Management of Business Activity of Territorial Communities: Case of Ukraine - VASKIVSKA, Katerуna; LYNDYUK, Andriy; DANYLIUK, Olena; KUCHER, Anatolii; VASKIVSKYY, Yuriy (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
The article analyzes challenges and prospects of development of business activity of territorial communities (hereinafter – TC) in terms of decentralization. Particular attention is paid to the extension of the opportunities for entrepreneurs due to the establishment of TC and in the context of implementation of the European Green Deal. The principal powers concerning support of economic development, solving environmental problems and supply of social services on the territory are delegated to the local bodies. It is a positive aspect, but it requires improvement of human resources of the local governmental bodies to secure efficient use of the provided opportunities. The research substantiates directions of business activation in TC, particularly creation of favorable environment for enterprises development at the state level, supply of broader access to financing for small and medium-size enterprises, simplification of tax administrating for small and medium-size enterprises, promotion of business culture and development of business skills and sustainable thinking, support for internationalization and greening of small and medium-size business, improvement of competitive capacity and innovative potential of enterprises. The work suggests a model of efficient management of business activity of territorial communities. The authors define the principal criteria for setting local taxes and charges at the level of community. The research also marks the problems that have a negative impact on business development of TC, particularly, restraints for business running, development of local infrastructure, and employment of population. The article specifies the reasons and factors of the obstacles appearance and proposes the ways for them overcoming.